A genetically identified population of layer 4 neurons in auditory cortex that contributes to pre-pulse inhibition of the acoustic startle response - Weible, Aldis P.; Yavorska, Iryna; Narayanan, Arthy; Wehr, Michael (Frontiers in Neural Circuits, 2022)
A fundamental task faced by the auditory system is the detection of events that are signaled by fluctuations in sound. Spiking in auditory cortical neurons is critical for sound detection, but the causal roles of specific cell types and circuits are still mostly unknown. Here we tested the role of a genetically-identified population of layer 4 auditory cortical neurons in sound detection. We measured sound detection using a common variant of pre-pulse inhibition of the acoustic startle response, in which a silent gap in background noise acts as a cue that attenuates startle. We used a Gpr26-Cre driver line, which we found expressed predominantly in layer 4 of auditory cortex. Photostimulation of these cells, which were responsive to gaps in noise, was sufficient to attenuate the startle reflex. Photosuppression of these cells reduced neural responses to gaps throughout cortex, and impaired behavioral gap detection. These data demonstrate that cortical Gpr26 neurons are both necessary and sufficient for top-down modulation of the acoustic startle reflex, and are thus likely to be involved in sound detection.